Mid-upper arm circumference at age of routine infant vaccination to identify infants at elevated risk of death: a retrospective cohort study in the Gambia - Martha K Mwangome; Greg Fegan; Tony Fulford; Andrew M Prentice; James A Berkley (Bulletin of the World Health Organization)
OBJECTIVE: To determine the predictive value for death before 12 months of age of mid-upper arm circumference (MUAC) and weight-for-length Z score (WFLz). METHODS: A retrospective cohort analysis of infants living in Keneba, in rural Gambia, was conducted. Anthropometric measures were obtained from demographic surveillance system records for infants registered between February 1974 and July 2008 who had had MUAC and WFLz recorded at 6-14 weeks of age and vital status recorded at least once more. Hazard ratios (HRs), population attributable fractions and areas under receiver operating characteristic (ROC) curves were estimated to assess the predictive value for death in infancy of MUAC and WFLz. FINDINGS: Of 2876 infants included in the analysis, 40 died before the age of 12 months. The HR for death in this group versus in well-nourished infants was 5.8 (95% confidence interval, CI: 1.6-21) for a WFLz < -3. HRs for MUACs below the thresholds of 115 mm, 110 mm and 105 mm were 4.5 (95% CI: 1.4-15), 9.5 (95% CI: 2.6-35) and 23 (95% CI: 4.2-122), respectively. The attributable fractions for a MUAC < 130 mm and a WFLz < 0 were 51% and 13%, respectively. The areas under the ROC curve for death in infancy were 0.55 (95% CI: 0.46 to 0.64) for WFLz and 0.64 (95% CI: 0.55 to 0.73) for MUAC. CONCLUSION: Among infants aged 6 to 14 weeks, unadjusted MUAC showed good performance in identifying infants at increased risk of death.